Pola Penggunaan Obat Antihipertensi di Puskesmas Boyolali - Risma Sakti Pambudi; Dwi Jayanti Indah Isnasari; Khotimatul Khusna (Yayasan Literasi Sains Indonesia, 2023)
Hypertension is known as a cardiovascular disease related to blood pressure and an unbalanced lifestyle. The incidence of hypertension in Indonesia is increasing. The goal of treating hypertension is to reduce mortality and morbidity. Pharmacological therapy that patients get can be in the form of a single antihypertensive drug or a combination of drugs. The purpose of this study was to look at the pattern of antihypertensive drug use at the Boyolali 1 Health Center. The method used was a retrospective descriptive method by looking at the patient's medical records for the period January-June 2022. Data obtained was then analyzed descriptively using percentages. Medical record data taken were 102 medical records. The results showed that the majority of hypertensive patients were women 66.67%, aged 46-55 35.29%, patients without comorbidities 82.35% and patients with stage 1 hypertension 73.53%. Regarding the pattern of use of hypertension drugs used, namely single drug therapy 66.67% with the highest use, namely amlodipine. While the most widely used combination drug was a combination of amlodipine and captopril 17.65%. The use of antihypertensive drugs is influenced by the clinical condition of each patient.